Kehamilan Tidak Diinginkan (KTD) Sebuah tinjauan Psikologi - Qibtiyah, Alimatul (Sunan Kalijaga State Islamic University & The Asia Foundation, 2003)
The problem of unwanted pregnancy, better known as abortion, is not easy to solve. This article discusses the differing opinions toward the issue of abortion. Abortion is a multidimensional and controversial issue, particularly when it is carried out for social reasons. This article claims that abortion may cause a psychological burden for clients undergoing the procedure, both before and after the event. The doctors, nurses and people who assist them may also feel this psychological burden. As such, before performing an abortion, for whatever reason, clients should have access to counselling as an effort to safeguard their reproductive health.